RETHINKING ACADEMIC ESSAY WRITING: SELECTED GENRES IN COMPARISON - Dedi Turmudi (Premise: Journal of English Education and Applied Linguistics, 2017)
How do opinion, discussion, and argumentative convince readers? How does each of them look different from each other seen from the generic structure, and language use? This conceptual paper is exploring how three selected genres in academic writing differ from each other. By reviewing journals of related topic of recently published, the writer convinces that opinion genre is less strong in persuading readers, and argumentative is very strong in assuring readers, whereas discussion is neutral in affecting readers The implication is that each genre has its own place to make readers satisfied and each of which indicates the level of ego and sophisticated countering back the statement called rebuttal and arguments and example. By reading this article readers will detect the tone of each genre and to what extent does each genre reach the readers’ mind. The implication is that any teacher or lecturer is best recommended to present this model, particularly in EFL context.